Literature Review Metode Reduksi Harmonisa Berbasis Kecerdasan Buatan pada Multilevel Inverter - Patrianaya Margayasa Wirsuyana, Gede; Linawati, Linawati; Bagus Gede Manuaba, Ida; Sari Hartati, Rukmi (Majalah Ilmiah Teknologi Elektro, 2022)
Multilevel inverter (MLI) is one type of inverter that has a multilevel output voltage. Although its better than conventional inverters, the MLIs operating at low frequency still contains low-order harmonics at the output voltage and current which have a negative impact on electrical system. To overcome these problems, Many researchers have developed various control and modulation techniques on inverters to reduce harmonics and minimize switching losses with the aim of optimizing inverter’s efficiency. Selective harmonic elimination pulse-width modulation (SHEPWM) is the most optimal control of all methods that have been developed to remove low-order harmonics from the inverter output voltage. However, there are challenges in the MLIs analysis process using SHEPWM because solving these equations is difficult. Bio-inspired intelligent algorithms (BIAs) is used to solve this problem. This paper describes in full a review of various studies that have been carried out previously related to the operating principle of nine types of BIA and their application in reducing harmonics. The conclusions has been made on the basis of information extracted from the literatures. All important information in this paper regarding harmonic reduction in MLI will help future research to design efficient power conversion systems. Keywords— Bio-inspired algorithm, harmonics, multilevel inverter, optimization, selective harmonic elimination.